Performance Evaluation of a Constructed Wetland Treating High-Ammonium Primary Domestic Wastewater Effluent - Spokas, L. A.; Veneman, P. L. M.; Simkins, S. C.; Long, S. C. (Water environment research, 2010)
An investigation of a top-loading, vertical-flow, submerged-bed constructed wetland system subject to a New York State discharge permit, of mineral nitrogen transformations occurring within the wetland units, and of the effects of local environment on system performance indicated 100% removal of biochemical oxygen demand (B0D) and mean 99.0 ± 1.1% removal of ammonium (NH 4 + ). The wetland system, located in Highland, New York, treats primary domestic wastewater effluent and consists of four beds presently operated in series. Influent and effluent samples from each of the four treatment units were analyzed for BOD, ammonium-nitrogen (NH 4 + -N), nitrate-nitrogen (NO 3 − -N), and nitrite-nitrogen (NO 2 − -N). During the study, mean influent wastewater concentrations were 170.8, 3.1, and 0.015 mg/L for NH 4 + -N, NO 3 − -N, and NO 2 − -N were 1.9, 4.2, and 0.002 mg/L, respectively.